The winner-take-all dilemma - Kazuya Kikuchi; Yukio Koriyama (Osaka University, Institute of Social and Economic Research (ISER), 2019)
This paper considers collective decision-making when individuals are partitioned into groups (e.g., states or parties) endowed with voting weights. We study a game in which each group chooses an internal rule that specifies the allocation of its weight to the alternatives as a function of its members' preferences. We show that under quite general conditions, the game is a Prisoner's Dilemma: while the winner-take-all rule is a dominant strategy, the equilibrium is Pareto dominated. We also show asymptotic Pareto dominance of the proportional rule. Our numerical computation for the US Electoral College verifies the sensibility of the asymptotic results.
Keywords: C72; D70; D72; 330; Representative democracy; winner-take-all rule; proportional rule